Chitosan Biopolymer and Its Nanocomposites: Emerging Material as Adsorbent in Wastewater Treatment - Indran Suyambulingam; Lekshmi Gangadhar; Siva Sankar Sana; Divya Divakaran; Suchart Siengchin; Lekshmi A. Kurup; Jenish Iyyadurai; K. E. Albert Bernad Noble (Advances in Materials Science and Engineering)
Water pollution is a global issue because of potentially lethal toxins. Polymeric nanomaterials are making their way into water treatment processes and are being utilized to efficiently remove a variety of pollutants. Polymeric nanomaterials are a popular option for a solution because they have a high adsorption capacity and a high surface charge. Nanocomposites have recently come to the attention of those working in the field of water treatment in order to more effectively remove contaminants. Polymeric composites are based on biopolymers and are being developed. These all quickly reached the industrial standards because of their low impact on the natural world. Chitosan is one of the biopolymers that are used extensively. Moreover, it is one of the most highly preferred biopolymers. It is simple to scale up and is readily available. The incorporation of nanomaterials into the biopolymer enables better control over the shape, size, and morphology of the particle, as well as an increase in the efficiency with which contaminants are removed. This is an excellent review that examines recent developments in the formation of chitosan-based polymeric nanocomposites and their performance in removing various contaminants including heavy metals, dyes, pesticides, pharmaceutical waste, and radionuclides from water.